Does decriminalized prostitution decrease new HIV cases? - Mangubat, Arra Mae M. (School of Economics, University of the Philippines Diliman, 2018)
Human Immunodeficiency Virus (HIV) is a type of virus that attacks the immune system. The medicine available today can only control but not cure HIV. Clients of sex workers serves as the _bridge population_ of HIV or other sexually transmitted diseases from sex workers to the general population. This paper analyzed how legalizing prostitution affects the number of recorded new HIV cases per capita in each country. Scale effect of legalized prostitution leads to an expansion of the industry thereby increasing new HIV cases per capita. Our study is a panel data of 61 countries from 1995 to 2015. Our empirical analysis shows that on average, there is a decrease in new HIV cases recorded per capita in countries where prostitution is legalized or decriminalized. Results also imply that a higher percentage of Muslim population in a country decreases the number of new HIV cases recorded per capita. Lastly, since regulation is not taken into account in the specification, lawmakers of States and Governments must consider other factors that affect the existence of HIV in their country. In doing so, they may be able to legislate using a mix of health, economic, and legal interventions that help curb new HIV cases.